The Effectiveness of a Program Based on the Theory of TRIZ in the Subject of Physics to Develop the Skills of Creative Thinking and Critical Thinking Among the Secondary School Students of the Southern Al-Mazar - aljaafreh, Itimad Jamil Al-Jaafreh Jamil (Journal of Education and Practice, 2020)
Purpose: The study aimed to learn about the effectiveness of a program based on the Theory of TRIZ in the subject of physics to develop the skills of creative thinking and critical thinking among the high school students of the Southern al-Mazar Brigade, the study used the design like experimental, and was represented the tools of study in the Torrance test for creative thinking and the test of California for critical thinking, as a training program was built based on the theory of creative solution to problems. Methodology: The sample of the study consisted of ( 81) students of the first high school scientific which was chosen in the method of intent and the students are distributed on two randomly assigned school divisions as exacts and pilots, one (40) students and the exact group, and the other (41) students represented the experimental group. Findings: The results of the study showed that there are statistically significant differences in favor of the experimental group that indicates the effectiveness of the program in developing the skills of creative thinking and Critical thinking among the students.